Efeitos do exercício físico sobre o processo inflamatório e sobre o déficit motor induzidos pelo traumatismo cranioencefálico em ratos - Mota, Bibiana Castagna (2013)
Traumatic brain injury (TBI) is a public health problem, and is considered a leading cause of death among children and young adults in industrialized countries. TBI can be defined as a mechanical external aggression to the brain, which may produce an altered state of consciousness leading the cognitive and / or motor impairment. In this context, the inflammatory process plays an important role in the development and exacerbation of secondary damage after TBI, mediating, through the release of cytokines, increased permeability of the blood brain barrier (BBB), edema formation and promoting the accumulation of leukocytes after TBI. Exercise provides protection on a variety of diseases and insults of the Central Nervous System (CNS). However, there are few studies showing the prophylactic effects of regular exercise on the damage caused by TBI. Therefore, the aim of this study was to investigate whether physical exercise protects against acute inflammatory response and motor impairment induced by TBI in rats. For this, the animals performed exercise for four weeks and then underwent the model of TBI by fluid percussion injury (FPI). Twenty-four hours after TBI the results showed that there was an impairment of motor function, followed by increased permeability of the BBB and brain inflammation characterized by increased levels of interleukin-1β (IL-1β ) of tumor necrosis factor-α (TNF-α) and by decreasing levels of interleukin-10 (IL-10). Furthermore, increased myeloperoxidase (MPO) and inhibition of enzyme activity Na+,K+-ATPase after TBI suggests that the opening of the BBB, followed by infiltration of neutrophils and brain inflammation may contribute to failure of selected targets leading to damage side. The results also demonstrated that physical exercise protected against motor impairment, BBB permeability and also protect against an increase in brain levels of IL-1β and TNF-α and decrease levels of IL-10 induced by fluid percussion injury (FPI) . This exercise protocol also protected the increase of MPO activity and inhibition of Na+,K+-ATPase after TBI. This protection correlated with decreased MPO activity, suggesting that a change in cerebral inflammatory profile, caused by physical exercise, may be reducing the initial injury and limiting secondary damage after TBI.